(untitled) (Baghdad Science Journal, 2023)
New Azo ligand (H2L) was synthesized by reacting the tryptamine diazonium salt with a compound 4-aminophenol. The characterization was conducted using element microanalysis as well as spectroscopic techniques (UV-Vis, FTIR, 1H & 13C-NMR, and LC-Mass) . Complexes for Ni,(II), Pd,(II), Pt,(IV), and Au,(III) were created and identified by using atomic absorption and elemental microanalysis .In addition spectral techniques (infrared, Mass, UV-Vis spectrum were used for magnetic and molar conductance measurements). Then using TGA and DSC curves was to examine the thermal stability of the compounds. Calculating the thermodynamic parameters ΔH, ΔS and ΔG included using the DCS curve. All complexes have a (1:1) metal-ligand ratio, and the molar conductance values indicated that all complexes have nonelectrolyte nature. The ligand functions in all complexes as a neutral bidentate moiety. From all the above techniques used in diagnosis, it was suggested that the nickel (II) and platin (IV) have an octahedral geometry while palladium(II)and Au(III) have a square planar geometry. The DPPH radical scavenging method will be used to assess the antioxidant activities of the ligand and metal complexes. These compounds showed antioxidant abilities to scavenge free radicals.